2021
DOI: 10.1080/21655979.2021.1953218
|View full text |Cite
|
Sign up to set email alerts
|

Ephedrine alleviates middle cerebral artery occlusion-induced neurological deficits and hippocampal neuronal damage in rats by activating PI3K/AKT signaling pathway

Abstract: Inflammation and oxidative stress are crucial in ischemic stroke. Ephedrine (EPH) has been proven to have anti-inflammatory and anti-oxidative stress effects. The present study analyzes whether EPH possessed neuroprotective effects and explored the underlying mechanisms of EPH based on an experimental model of middle cerebral artery occlusion (MCAO). We found that intraperitoneal injection with EPH attenuated the neurological deficit, cerebral infarction, and cerebral edema induced by MCAO in rats. Besides, EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In other words, the upregulated miR-137 promoted the phosphorylation of PI3K/Akt pathway, and INPP4B may not be the unique link bridging both of them. This also stresses a notion that all the results of bioinformatic analysis must be verified by both cell and animal experiments (33,50).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In other words, the upregulated miR-137 promoted the phosphorylation of PI3K/Akt pathway, and INPP4B may not be the unique link bridging both of them. This also stresses a notion that all the results of bioinformatic analysis must be verified by both cell and animal experiments (33,50).…”
Section: Discussionmentioning
confidence: 77%
“…The standard Western blot method was based on the previous literature ( 33 ). Hippocampus tissues or cultured cells were quickly dissected out on ice, and lysed in radioimmuno-precipitation assay (RIPA) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway has been proposed to modulate diverse biological processes and plays a key role in podocyte apoptosis, which is connected with the progress of proteinuria and renal function [ 51 ]. It has been reported that EH exerts anti-inflammatory and antioxidative stress effects through promoting the phosphorylation of PI3K and AKT proteins [ 52 ]. As the main component of EH, quercetin has been proved to improve renal fibrosis and apoptosis in chronic renal failure rats, as well as reducing water retention and toxin accumulation by inhibiting the PI3k/Akt pathway through targeting PIK3R [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, cells were mixed with 0.25 mg/ml MTT (Sigma-Aldrich, Missouri, USA) at 37°C for 3 h, and the medium was removed, followed by adding the dimethyl sulfoxide (DMSO) for the production of blue formazan. Lastly, the OD value at 630 nm was measured by the microplate reader (Mindray, Shenzhen, China) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%